Basis And Argument Leading to Therapeutic Utilities: Analysing Parallels between Depression and Alzheimer’s Disease, Role of Different Genomic Vulnerabilities - Roberto Rodrigues; George Perry; Robert Petersen (Medical Science: Trends and Innovations Vol. 5, 2025)
Alzheimer’s disease is a progressive, cumulative and irreversible illness in terms of Amyloid and hyperphosphorylated Tau and macromolecular ApoE complexes deposition on some structures in brain. This study is a brief report about the conclusions in which we have engaged from considering that Alzheimer’s disease, cognitive impairment and aging could progress with analogous molecular signaling, with no frontiers between their phenotypes. Progressively with aging, very mild and not significant cognitive distress starts appearing, which could be named sub-clinical or sub-threshold phase. With increasing age, cognitive and some emotional signs appear more clearly and progressively – it would be aging cognitive impairment (ACI) and mild cognitive impairment (MCI), clinical stages that are limitless in the ascendant range of intensity and may sometimes confuse physicians. Finally, the spectrum progresses to the known Alzheimer’s disease symptoms, which also are progressively stronger and most harmful to the individual, only finishing with death. It has also been proposed that chronic depression, with or no anxiety and/or stress comorbid indication may interact with these AD manifestations - already product of genomic vulnerability - at any stage of the disease. A known example may be mutant short alleles on the depression genes corresponding to the synthesis of a series of neurotransmitter transporters, particularly 5-HTTs – serotonin transporter proteins - which determine impaired inhibition of 5-HT at the neuron synapse and a decline of serotonin on the brain. AD, cognitive impairment - interacting with aging - have some molecular cascades that may join the Depression cascades and vice-versa when both neuronal pathologies are predisposed together to genomic disturbances, one phenotype reinforcing the other. It is also suggested that this model could be approached through new therapeutic strategies based on the interaction between the genotypes and phenotypes of these two illnesses, aging, and oxidative stress. Future research based on this model can contribute to bringing more control and prevention for both these neuropsychiatric pathologies.